2020
DOI: 10.3389/fbioe.2020.586534
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Point Control for Step-Down Perturbations and Downhill Slopes in Bipedal Running

Abstract: Bipedal running is a difficult task to realize in robots, since the trunk is underactuated and control is limited by intermittent ground contacts. Stabilizing the trunk becomes even more challenging if the terrain is uneven and causes perturbations. One bio-inspired method to achieve postural stability is the virtual point (VP) control, which is able to generate natural motion. However, so far it has only been studied for level running. In this work, we investigate whether the VP control method can accommodate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Finally, if the VPP is placed caudally to the proximal pivot, as depicted in dogs’ thoracic limb, the torque generated will absorb energy. In this case the leg must add energy axially to the system for the sake of periodicity (Blickhan et al, 2015; Drama and Badri-Spröwitz, 2020). Accordingly, the dogs under study here, except Whippets during walk, add energy axially to the system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, if the VPP is placed caudally to the proximal pivot, as depicted in dogs’ thoracic limb, the torque generated will absorb energy. In this case the leg must add energy axially to the system for the sake of periodicity (Blickhan et al, 2015; Drama and Badri-Spröwitz, 2020). Accordingly, the dogs under study here, except Whippets during walk, add energy axially to the system.…”
Section: Discussionmentioning
confidence: 99%
“…In bipeds, VPP as the target of control simplifies the balance of the trunk by changing an inverted pendulum control problem into a suspended one. Moreover, simulation studies based on this bio-inspired strategy showed that VPP control can balance not only the trunk but also generate stable bipedal gaits (Andrada et al, 2014; Drama and Badri-Spröwitz, 2020; Maus et al, 2010). So far, the existence of a VPP in quadrupedal locomotion has not been demonstrated experimentally.…”
Section: Introductionmentioning
confidence: 99%